COMPOSITION AND STRUCTURE OF THE EAST-CENTRAL EUROPEAN CONSTITUTIONAL COURTS - Toth, Zoltan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Abstract: The present paper is going to deal with the composition, the recruitment base, the operational mechanisms and the innen structure of the constitutional courts in the course of constitutional adjudication of eight East-Central European countries (in alphabetical order: Croatia, the Czech Republic, Hungary, Poland, Romania, Serbia, Slovakia, Slovenia), from a comparative law perspective. Despite their partially different historical past and the distinctions in the existence of predecessor institutions (or the lack therof), the inner organizational arrangements of the constitutional courts of the states analyzed and the rules of recruitment of constitutional judges therein show considerable similarity across the region.
Keywords: constitutional adjudication; constitutional courts; election of members and presidents of constitutional corts; East-Central Europe